A Study on X-ray Shielding Efficiency of New 3D Alloy. Issue 1 (1st January 2023) - Liu, Minqiang; Zhu, Xiaofeng; Zeng, Chao; Xu, Xianguo
Abstract: In this paper, MCNP was used to simulate the shielding efficiency of different shielding materials and the new 3D alloy (an alloy of Ta and W) with different surface densities for the low energy X-ray spectrum (<200keV), and the transmission efficiency of the new 3D alloy with different single energy X-ray spectrum. The simulation results show that the new 3D alloy is a shielding material with high X-ray shielding efficiency, which is approximate to W. The higher the surface density is, the greater the shielding efficiency of the new 3D alloy is. With the increase of energy, the X-ray transmissivity increases. At about 69keV, the transmissivity suddenly decreases to the minimum, and then increases with the increase of energy. And the X-ray transmission verification experiment is designed, and the experimental results are in good agreement with the simulation results.